2010
DOI: 10.1159/000275686
|View full text |Cite
|
Sign up to set email alerts
|

Walking for the Assessment of Balance in Healthy Subjects Older than 40 Years

Abstract: Background: The Berg scale and the timed ‘up and go’ test (TUG) are established measures to assess mobility in frail older adults. As an alternative to self-paced tests to assess aerobic exercise capacity, the incremental shuttle walk test (ISWT) was developed. We hypothesized that ISWT may be useful for the assessment of aerobic capacity and balance simultaneously in healthy adults. Objectives: There are 3 objectives: (1) to evaluate the intra-tester reliability of TUG in healthy subjects; (2) to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
(38 reference statements)
4
29
0
1
Order By: Relevance
“…Additionally, it was also observed that the tests commonly used for evaluating physical mobility, such as the TUG and the BBS, showed consistent correlations with the ISWD. Spagnuolo et al 9 observed that the ISWD was significantly correlated with the TUG (r=0.65; p<0.0001) and with the BBS score (r=0.61; p=0.003) in healthy elderly. The present results suggest the usefulness of the ISWT for the simultaneous evaluation of cardiorespiratory fitness and balance in this age group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, it was also observed that the tests commonly used for evaluating physical mobility, such as the TUG and the BBS, showed consistent correlations with the ISWD. Spagnuolo et al 9 observed that the ISWD was significantly correlated with the TUG (r=0.65; p<0.0001) and with the BBS score (r=0.61; p=0.003) in healthy elderly. The present results suggest the usefulness of the ISWT for the simultaneous evaluation of cardiorespiratory fitness and balance in this age group.…”
Section: Discussionmentioning
confidence: 97%
“…The Incremental Shuttle Walk Test (ISWT) was developed by Singh et al 8 . Recently, Spagnuolo et al 9 observed that the distance walked on the ISWT was correlated with balance (r=0.61) evaluated through the Berg Balance Scale (BBS). This correlation was similar to the one observed between the performances of the TUG and the BBS (r=-0.65).…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura foram encontrados resultados semelhantes na população idosa como: Berg et al 34 (r = -0,76), Podsiadlo e Richardson 26 (r = -0,81), O'Sullivan et al 35 ( = -0,767, p = 0,0001), Hatch et al 36 (r = 0,810, p < 0,01), Desai et al 37 (= -0,62), Spagnuolo et al 38 (r = -0,65, p < 0,05), Silva et al 39 (r = -0,301, p = 0,005), Gazzola et al 40 (r = -0,813, p < 0,05), Brusse et al 41 em idosos com Parkinson (= -0,78, p < 0,001), Gazzola et al 42 em idosos com disfunção vestibular crônica (r = -0,709, p < 0,001). Foi encontrado apenas um estudo de Karuka et al 43 em idosas que não encontraram correlação signifi cativa entre Berg e TUG (= -0,30, p = 0,10).…”
Section: Discussionunclassified
“…It is suggested that there is a consistent correlation between TUG and another index from of balance, for example, the distance covered in the incremental shuttle walk test (ISWT) and performance on Berg Balance Scale (BBS) in adult individuals and asymptomatic elderly (3). This is due to the incremental nature of ISWT, which demands agility to execute the changes of direction, as well the association already established between performance on tests of walking and balance (3,11).…”
Section: Introductionmentioning
confidence: 97%
“…This is due to the incremental nature of ISWT, which demands agility to execute the changes of direction, as well the association already established between performance on tests of walking and balance (3,11). Individuals with a history of falls have lower performance, compared to people who did not fall (11).…”
Section: Introductionmentioning
confidence: 99%